IMPLIKASI PENCEGAHAN KECURANGAN DANA DESA DENGAN PELAPORAN YANG TRANSPARAN DAN KOMITMEN DALAM BEROGANISASI - Rahmawan, Faris; Syaiful Akbar, Fajar (SUSTAINABLE, 2024)
This research aims to understand the implications or influence of transparent reporting and organizational commitment on preventing village fund fraud. The research used a quantitative method with the population in this study consisting of all village officials in Palang District totaling 197 people by taking 72 samples using a purposive sampling technique which requires the duties and main duties of village officials who have a role in village funds. This research uses primary data, namely through a questionnaire by conducting analysis using the SPSS version 26 application with multiple linear regression analysis. The results of the analysis show that transparent reporting has a relationship or influence, while commitment within the organization has no relationship or no influence on preventing village fund fraud.